An unexpected and devastating adverse event of dasatinib: Rhabdomyolysis - Uz, Burak; Dolasik, Ilhan (Elsevier Ltd, 2016)
We, herein, describe a 52-year-old male whom developed rhabdomyolysis and acute renal failure likely related to dasatinib shortly after the administration of treatment. Afterwithdrawal of dasatinib, the myalgia reduced, and his CK returned to normal levels within a week. On follow-up acute renal failure did resolve without requiring dialysis, but unfortunately the patient died of severe respiratory distress. We recommend that musculoskeletal symptoms should be monitorized during therapy with dasatinib, and CML patients with musculoskeletal symptoms shouldhave CK levels checked in order to prevent this unexpected but devastating adverse event. © 2015 The Authors.
Keywords: Creatine kinase; Dasatinib; Rhabdomyolysis